Efficient photocatalytic energy harvesting for air purification and electrical generation - Wei Wei; Niansi Li; Xuhui Cao; Guoyu Zhang; Bendong Yu; Jie Ji; Xudong Zhao (Nexus)
Ensuring good indoor air quality is crucial for human health because approximately 90% of humans’ time is spent indoors. Solar photocatalytic oxidation is one of the effective air purification methods to remove indoor air pollutants, but the solar utilization efficiency is low due to the limited photoresponse range on the solar spectrum and most nonutilized photocatalytic generated heat. To address this, we propose an innovative energy-harvesting approach utilizing photocatalytic interface for simultaneous indoor air purification and 24-h power generation by synergistically combining photocatalytic oxidation, thermoelectric power generation, and heat absorption/release of phase change material (PC-TEG-PCM). The photocatalytic interface effectively achieves a high pollutant removal ratio of 77% in the visible light range (<760 nm) and recovers 71.5% of solar energy, while the thermoelectric generator module reaches a maximum power generation efficiency of 0.4% under an irradiation of 1,000 W/m2. We further demonstrate the energy-harvesting performance of a rooftop-installed PC-TEG-PCM device, achieving an air purification rate of 40 m³/(h · m2), with a daytime power density of 2.5 W/m2 and a nighttime power density of 0.5 W/m2. Finally, the energy-saving impact of this system within a Chinese operational context demonstrates that achieving an annual clean air volume of 16,057–28,777 m3 and power generation of 149.9–291.4 W/m2 across China results in significant energy savings and environmental benefits. Broader context: Developing sustainable building solutions that prioritize both energy efficiency and indoor air quality (IAQ) is a key focus in modern urban development. With increasing awareness of the health risks posed by indoor air pollutants, reducing reliance on energy-intensive ventilation systems by directly lowering pollutant levels is gaining traction. Solar-driven photocatalytic air purification technologies show great promise for removing harmful volatile organic compounds from indoor environments. However, their limited solar spectrum utilization and inefficient energy conversion hinder widespread application. This study presents a groundbreaking hybrid system that integrates photocatalytic oxidation, thermoelectric generation, and phase change materials, offering a dual solution of air purification and continuous 24-h power generation. By maximizing energy harvesting from the solar photocatalysis interface, the system not only achieves high pollutant removal rates and efficient energy recovery but also addresses the challenges of heat waste and limited solar utilization. This advancement has significant implications for reducing building energy consumption, improving IAQ, and contributing to the broader goals of energy and environmental sustainability.